Evaluation of Messages to Promote Intake of Calcium-Rich Foods in Early Adolescents - Yannica Martinez; Jinan C. Banna; Miriam E. Ballejos; Christine Bruhn; Mary Cluskey; Carolyn Gunther; Nobuko Kay Hongu; N. Paul Johnston; Scottie Misner; Marla Reicks; Rickelle Richards; Siew Sun Wong (The University of Alabama, 2022)
Parental practices influence intake of calcium-rich foods and beverages (CRFB) in adolescents. This study aimed to test two posters promoting such parental practices for comprehension, cultural and personal relevance, and ability to motivate parents to encourage CRFB intake. Interviews were conducted with 14 Hispanic and 6 Asian parents to evaluate two posters entitled "Good play starts with calcium" and "Strong families start with good nutrition." Responses were reviewed for themes. For "Good play," both racial/ethnic groups of parents understood the message to provide CRFB. Only Hispanics, however, recognized the connection between calcium and strong bones. For "Strong families," both groups had difficulty understanding that foods pictured were calcium rich. Both posters were considered culturally and personally relevant; however, not all respondents indicated motivation to provide CRFB. Modifications are needed to emphasize the connection between images and taglines and calcium intake for use in a future intervention to improve CRFB-promoting practices.